Project based learning berorientasi ESD: peran guru IPS dalam meningkatkan komunikasi dan kolaborasi siswa - Junima Tesalonika Sihombing; Neiny Ratmaningsih; Acep Supriadi (Journal of Educational and Learning Studies, 2025)
This research aims to describe the role of social studies teachers in improving students' communication and collaboration skills through project based learning oriented towards education for sustainable development. The research approach used in this research is qualitative and the method used is descriptive. The data collection techniques used in this research are observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions or verification. The research results show that the role of social studies teachers is in improving communication and collaboration skills through ESD-oriented project based learning by paying attention to the stages of project-based learning on aspects of communication and collaboration. These stages do not escape the orientation of education for sustainable development with the hope that students will be more concerned and aware of the environmental, social and economic problems they face.